Court Decision to Replace the Deed of Sale and Purchase of Land in the Agreement and Switch of Cessie Rights - Kholida Nabila; Muhammad Sofyan Pulungan; Isyana Wisnuwardhani Sadjarwo (Susbtantive Justice International Journal of Law, 2021)
Deed of Recognition of Debt is a deed that is generally made by the notary public, followed by binding guarantees that are attached (accessoir) the main agreement. In practice, the Deed of Recognition of Debt can be transferred to another party who is willing to buy it, so that The Sale and Purchase Agreement of Rights to Cessie and Agreements of Transfer of Rights to Cessie is notarized made. The last party who has the cessie rights sometimes does not get his rights because the debtor is no longer known to exist. That is why the party who has the cessie rights claims it to District Court so that it can be determined as the owner of the object of collateral. This case happened at the North Jakarta District Court No. 123/Pdt.G/2018/PN. JKT.UTR where the Panel of Judges decided that the Court's Decision could be a substitute of the land deed sell and purchase based on the sale and purchase agreement of rights to cessie and agreements of transfer of rights to cessie. This court decision is certainly a new legal breakthrough, especially in the notarial and land affairs fields. This type of research is normative with qualitative data analysis, and concluding deductive means. Based on the author's analysis, The Sale and Purchase Agreement of Rights to Cessie and Agreements of Transfer of Rights to Cessie is valid is authentic deeds that are valid and in accordance with applicable law. The public notaries also run their authority properly, so that the deeds have fulfilled the external, formal, and material aspects. Land deed officer who will make the deed on Land Certificate Number. 5217/Bojongnangka has been protected by law because the Land deed officer is obliged to obey the Decision of the Panel of Judges as the competent general authority, and the land deed officer only run his authority after the Land Office of Tangerang Regency has processed the owner's name change of initials TN to SS.